Global diversity and biogeography of Lyophyllum inferred from amplicon datasets - Wei, Shuwei; Qi, Bao; Zhang, Xiaozhuo; Peng, Zhanwu; Li, Yu; Wang, Qi (Frontiers in Ecology and Evolution, 2024)
Lyophyllum consists of rare edible and medicinal mushrooms. Considering this group’s economic and ecological significance, understanding its biodiversity could be strategically important. Our analysis involved an extensive examination of publicly available ITS sequences from NCBI-GenBank and fungal amplicon sequencing data obtained from NCBI-SRA. At a 98% sequence simi-larity level, we deliminated 88 Lyophyllum OTUs, 49 of which were not categorized as ‘known spe-cies’. The diversity of Lyophyllum is predominantly concentrated in the Northern Hemisphere and tends to display endemic distribution, and Europe is particularly notable for its high diversity of Ly-ophyllum. Given the escalating volume of data produced by amplicon sequencing, employing the amplicon dataset can facilitate an accurate survey of species diversity in Lyophyllum taxonomy. By using data from amplicon datasets, the fieldwork time and research funding for taxonomists can be saved, thereby significantly advancing the progress of the entire field of biodiversity research.